O papel do mediador nas tertúlias literárias: uma experiência de encantamento e transformação do leitor - Elias, Cristiane Casquet de Souza (2022)
The present research approaches the literary word as a motivator for the construction of dialogues and personal interactions. The study is based on gatherings promoted by the Tertúlias Literárias, with the presence of a mediator, whose literary knowledge and his interventions in the reading process favor discussion, interpretation and attribution of meaning to the text. The hypothesis of this research is that the methodology proposed by the Tertúlias Literárias associated with the presence of a mediator, whose function is to welcome and articulate the participants’ speech, would awaken more specifically the literary view, expanding the possibilities of understanding and meaning of the assessed works. Encouraging reflection and dialogue, as well as the power of argumentation of ideas and the construction of critical thinking, would be ways to make the reader's perception a transforming reading experience, whether in relation to themselves or to their interlocutors, or still in relation to their way of placing themselves in the world. To support this study, Mikhail Bakhtin's theoretical assumptions and his conception of language will be addressed, as well as some of his fundamental concepts for literary theory, such as polyphony, dialogism and alterity; in addition to Paulo Freire's studies on the importance of the act of reading and the role of the reader. Ramón Flecha and his scientific investigations based on theories and practices that overcome inequality will be our theoretical support for the study of Tertúlias Dialógicas Literárias and for the conception of Dialogical Learning. Finally, Antonio Candido and his defense of the right to literature, as a basic human need, is the tone that will conduct this research